OPTIMASI PROSES SELEKSI PEGAWAI MENGGUNAKAN SISTEM PENDUKUNG KEPUTUSAN METODE COPRAS - Andriyani, Wahyu Fitri; Sihombing, Volvo; Juledi, Angga Putra (Politeknik Bisnis Indonesia, 2024)
This study aims to develop a decision support system (DSS) based on the COPRAS method to help simplify the employee selection process at SPX Express, Rokan Hilir. The challenges faced in the selection process are subjectivity in assessment and non-integration of data, which results in less than optimal selection decisions. The COPRAS method is used to evaluate candidates based on predetermined criteria, such as Personality Tests, Health Tests, Knowledge Tests, Age, and Work Experience. This study involves the stages of determining the weight of the criteria, collecting data, and processing data using the COPRAS method to produce candidate rankings. The results showed that the candidates with the highest rankings were CP_02, CP_01, and CP_05. This DSS system can improve efficiency and objectivity in employee selection decision making.